Central Auditory and Vestibular Dysfunction Are Key Features of Autism Spectrum Disorder - Mansour, Yusra; Burchell, Alyson; Kulesza, Randy J. (Frontiers in Integrative Neuroscience, 2021)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by repetitive behaviors, poor social skills, and difficulties with communication. Beyond these core signs and symptoms, the majority of subjects with ASD have some degree of auditory and vestibular dysfunction. Dysfunction in these sensory modalities is significant as normal cognitive development depends on an accurate representation of our environment. The hearing difficulties in ASD range from deafness to hypersensitivity and subjects with ASD have abnormal sound-evoked brainstem reflexes and brainstem auditory evoked potentials. Vestibular dysfunction in ASD includes postural instability, gait dysfunction, and impaired gaze. Untreated vestibular dysfunction in children can lead to delayed milestones such as sitting and walking and poor motor coordination later in life. Histopathological studies have revealed that subjects with ASD have significantly fewer neurons in the auditory hindbrain and surviving neurons are smaller and dysmorphic. These findings are consistent with auditory dysfunction. Further, the cerebellum was one of the first brain structures implicated in ASD and studies have revealed loss of Purkinje cells and the presence of ectopic neurons. Together, these studies suggest that normal auditory and vestibular function play major roles in the development of language and social abilities, and dysfunction in these systems may contribute to the core symptoms of ASD. Further, auditory and vestibular dysfunction in children may be overlooked or attributed to other neurodevelopmental disorders. Herein we review the literature on auditory and vestibular dysfunction in ASD. Based on these results we developed a brainstem model of central auditory and vestibular dysfunction in ASD and propose that simple, non-invasive but quantitative testing of hearing and vestibular function be added to newborn screening protocols.